Assessment of Effect of COVID 19 Pandemic on the Utilization of Maternal Newborn and Child Health Services in Somali Region of Ethiopia - Olusola Oladeji; Bibilola Oladeji; Abdifatah Elmi Farah; Yusuf Mohammed Ali; Mohamed Ayanle (Masters Program in Public Health, 2020)
Background: Somali Region of Ethiopia recorded the first confirmed case of SARS-CoV-2 (COVID 19) pandemic on 26th April 2020. The study aimed to assess the effect of the pandemic on the utilization of maternal new-born and child health services.Subjects and Method: This was a retrospective chart review of monthly DHIS database of health facilities in Farfan zone of Somali Region and test of association using t test was used to compare the mean reduction in utilization of maternal and child health services three months before (January